Factors influencing implementation of accrual based international public sector accounting standards in Tanzanian local government authorities - Komba, Gabriel Vitus; Matekele, Charles K. (Asian Journal of Economics, Business and Accounting, 2024)
This work was carried out in collaboration between both authors. Author CKM designed the study, performed the statistical analysis, wrote the protocol and wrote the first draft of the manuscript. Author GVK managed the analyses of the study and literature searches. Both authors read and approved the final manuscript.